2015
DOI: 10.1108/ijrdm-11-2013-0212
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of product claims between private label and national brands

Abstract: Purpose – The purpose of this paper is to compare the use of front of package (FOP) claims within product categories by private label (PL) products and national brands (NB). This research adapts an existing conceptual model exploring the marketing strategies of PL products and NBs. Design/methodology/approach – Information for this study came from Mintel’s Global (2009/2011). There were 10,791 products launched in 2011 in the US database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Retailers have already increased SBs' shelf spacing to convince such consumers to buy these products (Nogales and Suarez, 2005; Schnittka, 2015). Now, they should invest the resources needed (Stanton et al , 2015) to heavily advertise SB products, through comparative advertising, to attract such consumers to their stores.…”
Section: Discussionmentioning
confidence: 99%
“…Retailers have already increased SBs' shelf spacing to convince such consumers to buy these products (Nogales and Suarez, 2005; Schnittka, 2015). Now, they should invest the resources needed (Stanton et al , 2015) to heavily advertise SB products, through comparative advertising, to attract such consumers to their stores.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, USV facilitates shoppers to enhance their purchase capability and increase their skills of searching for products in terms of convenience, savings and quality (Chandon et al, 2002). In addition, since price part engages in the decision of choosing of PL product, therefore getting the shopping experience of utilitarian benefits has a long-lasting influence on the purchase decision regarding PL products (Stanton, 2015). Cuneo et al, (2013) found that Shoppers choose products with greater values that can get advanced benefits that product can transmit to them.…”
Section: The Influence Of Utilitarian Shopping Value As a Moderator Omentioning
confidence: 99%
“…(Ailawadi et al, 2009, Ellickson et al, 2017. The PL products were mostly spread in the USA, initiated as early as the 1860s (Stanton, 2015;Knuth, 1987;Connor et al, 1996). Western Europe has experienced the most tremendous growth in market share with Switzerland having 45% share of the PL market.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies of new product launches have documented an increased prevalence of FOP references on these products in recent years (Van Camp et al 2011;Stanton et al 2015), and there is some indication that FOP references are particularly prevalent on novel, substitute foods. An examination of "novel beverages" sold in Canadian grocery stores, for instance, found that nearly all energy drinks, vitamin waters, and nutrient-enhanced fruit beverages displayed some form of nutrition reference, in stark contrast to research reporting that only a third of traditional fruit juices bore nutrition references (Dachner et al 2015).…”
Section: Introductionmentioning
confidence: 99%